The OSE complotype and its clinical potential - Alic, Lejla; Binder, Christoph J.; Papac-Milicevic, Nikolina (Frontiers in Immunology, 2022)
Cellular death, aging, and tissue damage trigger inflammation that leads to enzymatic and non-enzymatic lipid peroxidation of polyunsaturated fatty acids present on cellular membranes and lipoproteins. This results in the generation of highly reactive degradation products, such as malondialdehyde (MDA) and 4-hydroxynonenal (4-HNE), that covalently modify free amino groups of proteins and lipids in their vicinity forming a unique set of DAMPs - oxidation-specific epitopes (OSEs). OSEs are enriched on oxidized lipoproteins, microvesicles, and dying cells, and trigger sterile inflammation. Therefore, prompt recognition and removal of OSEs is required to maintain the homeostatic balance. This is partially achieved by various humoral components of the innate immune system, such as natural IgM antibodies, pentraxins, and complement components. Natural IgM antibodies are potent complement activators, and 30% of them recognize OSEs. Furthermore, OxPC-epitopes bind C-reactive protein, while MDA-epitopes are bound by C1q, C3a, complement factor H (CFH), and complement factor H-related proteins 1, 3, 5 (FHR-1, FHR-3, FHR-5). In addition, CFH and FHR-3 are recruited to 2-(ω-carboxyethyl)pyrrole (CEP), and CFH attenuates 4-HNE-induced oxidative stress. Consequently, alterations in the innate humoral defense against OSEs predispose to the development of oxidative stress-related diseases. In this mini-review, we focus on the mechanisms of the accumulation of OSEs, the pathophysiological consequences, and the interactions between different OSEs and complement components. Additionally, we will discuss the clinical potential of genetic variants in OSE-recognizing complement proteins – the OSE complotype - in the risk estimation of diseases associated with oxidative stress.